Urgensi Literasi Digital Bagi Anak Usia Dini Dan Orang Tua - Julita Lindriany; Dian Hidayati; Datuk Muhammad Nasaruddin (Journal of Education and Teaching (JET), 2023)
The purpose of this study is to describe the importance of digital literacy for early childhood in training children's intelligence, psychology, language skills, cognitive, emotional, social, academic and critical. The research method used is a descriptive qualitative procedure. Data collection techniques used were observation and interviews involving 5 parents of students. Data analysis includes stages: collection, reduction, display, and conclusion. The results of the study show the importance of digital literacy for early childhood and parents in training children's intelligence, psychologically, language skills, cognitive, emotional, social, academic and critical, children's cognitive abilities increase and language skills become better and make it easier for people Parents are looking for content containing stories, pictures, songs, etc. that are appropriate for young children. Digital literacy is very important to be developed by all elements in the world of education.